Patterns of homicidal deaths in population of western UttarPradesh - Sangal , Abhishek; Ghosh , Mithun; Bansal , P K; Srivastava, A K; Singh, Bhim (Journal of Indian Academy of Forensic Medicine, 2019)
Homicides are common cause of loss of human lives since ancient times. This study was conducted to find out the method, cause and  circumstances causing homicidal deaths in present era, especially in Northern Uttar Pradesh. A total of 227 homicidal deaths were  studied for epidemiological and medico-legal aspects in dead bodies brought to the mortuary of LLRM Medical College, Meerut for  medico-legal autopsies between June 2017 to October 2018. All the data thus collected was compiled and analysed in detail. The  majority of the victims (70.92%) were males, and young adults (60.34%) between 21–40 years of age. Sharp edged weapons (50.66%)  and firearms (29.96%) were used in the majority of the homicidal victims. Assailants had tried to hit on vital areas in almost all the  cases, of which multiple areas were involved in more than 2/3 (69.61%) of the cases. Head was the commonest individual body involved in 18.06% cases of homicides. Haemorrhage and shock were the most common cause of death (62.99%) and disputes on  money and/or property remained the most important reason behind the homicides (23.34% cases).
Keywords: Homicide; Firearms; Sharp-edged weapon; Shock; Haemorrhage; Disputes on property